1995
DOI: 10.1523/jneurosci.15-10-06975.1995
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and pharmacological analysis of neurotransmitters controlling egg laying in C. elegans

Abstract: We have investigated the neurotransmitters used to control egg-laying in C. elegans. Previous studies suggested that 5-HT released by the HSN motor neurons stimulates egg laying, and that tricyclic antidepressants potentiate egg laying by blocking reuptake of 5-HT by the HSN neurons. We report studies of the wild type and a mutant that lacks detectable 5-HT that suggest 5-HT is not required for egglaying. Furthermore, we find that ACh is required for egg laying in response to 5-HT, suggesting that 5-HT is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
193
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(216 citation statements)
references
References 27 publications
11
193
0
1
Order By: Relevance
“…The egl-2(gf) allele induces egg retention in hermaphrodites as well as defecation and chemotaxis defects (Reiner et al 1995;Weinshenker et al 1995; Mean gray level of DsRed-E5 fluorescent protein expression in the male tail. DsRed-E5 initially expresses in the green channel and then shifts its emission spectra to the red channel.…”
Section: Resultsmentioning
confidence: 99%
“…The egl-2(gf) allele induces egg retention in hermaphrodites as well as defecation and chemotaxis defects (Reiner et al 1995;Weinshenker et al 1995; Mean gray level of DsRed-E5 fluorescent protein expression in the male tail. DsRed-E5 initially expresses in the green channel and then shifts its emission spectra to the red channel.…”
Section: Resultsmentioning
confidence: 99%
“…None of these drugs appreciably inhibited DAF-16::GFP nuclear accumulation. Weinshenker et al (39) demonstrated that fluoxetine is taken up by C. elegans, and all of these control drugs can cross the blood-brain barrier in mammals.…”
Section: Resultsmentioning
confidence: 99%
“…Dopamine plays a significant role in C. elegans behaviors, including locomotion, egg laying, and the basal slowing response to food (Schafer and Kenyon, 1995;Weinshenker et al, 1995;Sawin et al, 2000). The C. elegans hermaphrodite has four bilaterally symmetrical pairs of dopaminergic neurons (ADE neurons, PDE neurons, and two pairs of CEP neurons) that appear to play a role in mechanosensation (Sulston et al, 1975;Sawin et al, 2000).…”
Section: Dopaminergic Signaling Is Required For Arsmentioning
confidence: 99%
“…In response to attractive stimuli, such as food, C. elegans modulates its turning frequency and navigates up a gradient of chemical cues (Croll, 1975;Pierce-Shimomura et al, 1999). Dopaminergic signaling mediates the locomotory response to food (Sawin et al, 2000) and also plays a role in feeding and egg laying (Schafer and Kenyon, 1995;Weinshenker et al, 1995). Four pairs of bilaterally symmetrical dopaminergic sensory neurons have been identified in the C. elegans hermaphrodite (Sulston et al, 1975).…”
Section: Introductionmentioning
confidence: 99%